Forging of hollow sintered powder preforms - Jha A.K.; Kumar S. (My University, 2025)
The forging of sintered metal powder preforms is currently arousing interest in many parts of the world as an economic method of producing components from metal powders. The present investigation has been undertaken with a view to studying the deformation characteristics of hollow sintered copper powder discs at room temperature. A theoretical analysis based on the energy method is presented for the estimation of deformation load using yield criterion for porous sintered materials and an appropriate interfacial friction law. Experiments have also been conducted which involved the forging of hollow discs of electrolytic copper powder at room temperature under axisymmetric conditions. In order to illustrate the validity of the theoretical approach, the theoretical and experimental results have been compared and presented graphically.